2016
DOI: 10.1371/journal.pone.0150565
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth and Low Birth Weight after In Utero Exposure to Antiretrovirals Initiated during Pregnancy in Yaoundé, Cameroon

Abstract: BackgroundEffects of antiretroviral therapy (ART) on birth outcomes remain controversial.ObjectiveTo assess the impact of antenatal exposure to ART on the occurrence of preterm birth (PTB) and low birth weight (LBW).MethodsA cross-sectional study conducted at the Essos Hospital Center in Yaounde from 2008 to 2011 among HIV vertically exposed infants with two distinct maternal antiretroviral experiences: monotherapy group (Zidovudine, ZDV) and the combination ART group (cART). Mothers already receiving cART bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
(38 reference statements)
2
7
0
Order By: Relevance
“…EFV‐based regimens have demonstrated a null or protective relationship with preterm birth when compared to nevirapine‐ or dolutegravir‐based regimens and are widely available. Among infants in our study, birth outcomes were comparable to or more favourable than results from other sub‐Saharan African countries for both preterm birth and low birth weight . We did not observe pregnancy outcomes for women lost to follow‐up, so our results may underestimate adverse birth outcomes and MTCT events.…”
Section: Discussionsupporting
confidence: 56%
“…EFV‐based regimens have demonstrated a null or protective relationship with preterm birth when compared to nevirapine‐ or dolutegravir‐based regimens and are widely available. Among infants in our study, birth outcomes were comparable to or more favourable than results from other sub‐Saharan African countries for both preterm birth and low birth weight . We did not observe pregnancy outcomes for women lost to follow‐up, so our results may underestimate adverse birth outcomes and MTCT events.…”
Section: Discussionsupporting
confidence: 56%
“…In our study, we found an association between maternal plasma levels of sCD14 during the second half of pregnancy and low neonatal birthweight. This association persisted ( P = .043) in a multivariate regression model adjusted for demographic and clinical characteristics known to be potential risk factors for low birthweight . To our knowledge, this is the first time that this association is observed in low‐income countries, where the role of systemic immune activation markers may be confounded by other factors, such as malnutrition and maternal comorbidities, including opportunistic infections and/or vector transmissible diseases.…”
Section: Discussionmentioning
confidence: 64%
“…The association between maternal levels of sCD14 and birthweight was tested using a multivariable linear regression model, controlling for potential confounding factors. The selection of potential confounding variables, including both demographic and clinical characteristics, was based on previous data and the available information in this study. Differences were considered statistically significant when P < .05.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that our sample size did not enable detection of small to moderate differences between these groups of women, however our results are consistent with findings from a previous South African cohort, 21 and findings from other settings. 35 This suggests that in our study population there might be minimal differences across the comparison group and that any GA measurement errors were equally distributed.…”
Section: Discussionmentioning
confidence: 80%